Fueling Cancer Immunotherapy With Common Gamma Chain Cytokines - Dwyer, Connor J.; Knochelmann, Hannah M.; Smith, Aubrey S.; Wyatt, Megan M.; Rangel Rivera, Guillermo O.; Arhontoulis, Dimitrios C.; Bartee, Eric; Li, Zihai; Rubinstein, Mark P.; Paulos, Chrystal M. (Frontiers in Immunology, 2019)
Adoptive T cell transfer therapy (ACT) using tumor infiltrating lymphocytes or lymphocytes redirected with antigen receptors (CAR or TCR) has revolutionized the field of cancer immunotherapy. Although CAR T cell therapy mediates robust responses in patients with hematological malignancies, this approach has been less effective for treating patients with solid tumors. Additionally, toxicities post T cell infusion highlight the need for safer ACT protocols. Current protocols traditionally expand T lymphocytes isolated from patient tumors or from peripheral blood to large magnitudes in the presence of high dose IL-2 prior to infusion. Unfortunately, this expansion protocol differentiates T cells to a full effector or terminal phenotype in vitro, consequently reducing their long-term survival and antitumor effectiveness in vivo. Post-infusion, T cells face further obstacles limiting their persistence and function within the suppressive tumor microenvironment. Therapeutic manipulation of T cells with common  chain cytokines, which are critical growth factors for T cells, may be the key to bypass such immunological hurdles. Herein, we discuss the primary functions of the common  chain cytokines impacting T cell survival and memory and then elaborate on how these distinct cytokines have been used to augment T cell-based cancer immunotherapy.